2013
DOI: 10.1155/2013/273712
|View full text |Cite
|
Sign up to set email alerts
|

Loranthus micranthusLinn.: Biological Activities and Phytochemistry

Abstract: Loranthus micranthus Linn. is a medicinal plant from the Loranthaceae family commonly known as an eastern Nigeria species of the African mistletoe and is widely used in folkloric medicine to cure various ailments and diseases. It is semiparasitic plant because of growing on various host trees and shrubs and absorbing mineral nutrition and water from respective host. Hence, the phytochemicals and biological activities of L. micranthus demonstrated strong host and harvesting period dependency. The leaves have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 53 publications
(54 reference statements)
2
42
0
Order By: Relevance
“…In a separate study, Ibrahim et al [52] found no Alkaloids in all 27 mistletoe representing seven different species obtained from different locations spread across eight cities/towns in Nigeria palpably confirms the findings in this study and several others [13,23,24,25,26].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In a separate study, Ibrahim et al [52] found no Alkaloids in all 27 mistletoe representing seven different species obtained from different locations spread across eight cities/towns in Nigeria palpably confirms the findings in this study and several others [13,23,24,25,26].…”
Section: Discussionsupporting
confidence: 89%
“…The contention that presence or accumulation of secondary metabolites in mistletoe depend on the season of the year, mode of extraction of secondary metabolites as well as mistletoe -host plant dependency [23,24] was accentuated as T. ogowenisis from M. oleifera recorded highest amount of alkaloids. Phytochemical studies on L. micranthus leaves harvested from six different host trees, namely, Persia americana, Baphia nitida, Kola acuminata, Pentaclethra macrophylla, Azadiratcha indica, and Irvingia gabonensis, revealed large quantities of alkaloids in the extracts of K. acuminata, P. americana, and I. gabonensis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical constituents were season-dependent, being highest during the peak of the rainy season [24]. In addition, several compounds, including alkaloids, steroids, terpenes and polyphenols have been isolated from the plant [25]. The level of phytochemicals in the leaf extracts ensured protective roles against oxidative stress associated with hyperglycemia.…”
Section: Data Are Presented As Mean ± Sem (N = 5) A= Extract From Avmentioning
confidence: 99%
“…They are semiparasitic plants and grow on various host trees and shrubs where they survive by depending on their respective host for mineral nutrition and water, although they produce their own carbohydrates through photosynthesis (Griggs, 1991). Mistletoe was described as "an all-purpose herb" due to its rich traditional uses and it has been widely used in ethnomedicine for various purposes, including antihypertensive, anticancer, antispasmodic, antidiabetic and for treatment of epilepsy, headache, infertility, menopausal syndrome and rheumatism (Moghadamtousi et al, 2013).…”
mentioning
confidence: 99%